European-wide inequality in times of the financial crisis - Timm Bönke; Carsten Schröder (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
In view of rising concerns over increasing inequality in the European Union since the financial crisis, this study provides an inequality decomposition of the overall European income distribution by country. The EU Statistics on Income and Living Conditions are our empirical basis. Inequality has risen moderately within the core Euro area, particularly in the last two years of the observation period (2010/11). Widening disparities between EU Member States are the driving force behind this trend, while inequalities within countries do not exhibit systematic changes. An analysis of binational distributions reveals that it is the countries hit worst by the crisis-Greece and Spain-for which the between-country disparities have changed most markedly.
Keywords: D30; D31; D39; 330; inequality; decomposition; crisis